ANALYSIS OF MATHEMATICS LEARNING OUTCOMES BASED ON LOCAL CULTURE ACCORDING TO POLYA THEORY - Anita Hutagaol (Universitas Asahan, 2022)
This research aims to obtain information on how much students make mistakes according to Polya's theory and to find out the causes of students making these mistakes. This type of research is qualitative research that is analyzed using a descriptive approach in problem research. The subjects of this research were class VIIIB SMPN 2 Sintang with 37 people, and the data analysis used descriptive qualitative. The results obtained are 89.3% of students' errors in understanding the problem, 41.5% of students' misconceptions in formulating problems, 32.2% of students making mistakes in carrying out plans and errors when checking back answered 36.4% of students. Factors causing these errors: (1) students are less interested in learning mathematics, (2) lack of talent in mathematics, (3) difficulty working on problems and (4) teachers' teaching methods are less varied in providing explanations about mathematics lessons, mainly based on local culture